Pre-operative Assessment of Ovarian Tumor in Patients Presenting with Adnexal Mass on the Basis of Risk of Malignancy Index (RMI) (Journal of Shaheed Suhrawardy Medical College, 2018)
Background:Ovarian cancer is the second most common gynaecologic cancer in developing countries. Five-year survival of ovarian cancer varies according to stages, hence, screening, detection and treatment in earlier stages are of great importance. The Scottish Intercollegiate Guidelines Network (SIGN) recommends use of Risk of Malignancy Index (RMI) for preoperative assessment of ovarian tumours. It is a scoring system based on menopausal status, ultrasound findings, and serum CA 125 level in adnexal mass.Objective:To investigate the accuracy of RMI as a predictive method of discriminating benign from malignant ovarian tumour.Methodology: Fifty patients, 30 years or older, with adnexal mass, admitted for laparotomy in Obstetrics and Gynaecology Dept. from April’13 to September’13were randomly assigned in this cross-sectional descriptive study. RMI was calculated for each patient based on menopausal status, CA125 level and ultrasound findings of bilateral lesion, multilocular cyst, solid areas, ascites and metastases.Results:Among 50 women, 18 cases (36%) were postmenopausal showing more malignant tumors (77.78%) in this group. Depending on histopathological reports, 82% benign and 18% malignant diseases.The best performance of RMI was obtained at cut-off value of 230 with sensitivity of 100%, specificity of 95.2%, positive predictive value (PPV) of 80% and negative predictive value (NPV) 100%. Conclusion:Compared to previous studies, RMI was highly sensitive in detecting malignant disease, though not as specific in excluding benign lesions, particularly endometriosis.J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 69-73